The Complete Mitochondrial Genome and Expression Profile of Mitochondrial Protein-Coding Genes in the Bisexual and Parthenogenetic Haemaphysalis longicornis - Wang, Tianhong; Zhang, Shiqi; Pei, Tingwei; Yu, Zhijun; Liu, Jingze (Frontiers in Physiology, 2019)
The tick Haemaphysalis longicornis is widely distributed in eastern Asia, New Zealand and Australia, and is notorious as a vector of multiple zoonotic pathogens. It exhibits two reproductive strategies, bisexual and obligate parthenogenetic population. Hence, in the current study, the complete mitochondrial genomes of the bisexual and parthenogenetic populations were assembled and analyzed, and the expression of the mitochondrial protein-coding genes was evaluated and compared with the two reproductive populations. Results indicated that the length of the mitochondrial genomes of the two reproductive populations is 14,694 bp and 14,693 bp in the bisexual and parthenogenetic population, respectively. The AT content in the mitochondrial genome of the bisexual and obligate parthenogenetic populations reached 77.22% and 77.34%, respectively. The Phylogenetic tree was constructed combing with 13 protein-coding genes, which showed that the genetic distance between bisexual and parthenogenetic populations was lower than subspecies. The expressions of the mitochondrial protein-coding genes were quantitatively analyzed at different feeding statuses of the bisexual and parthenogenetic population, and results showed significant differences in expression patterns of these genes, suggesting that they might trigger specific energy utilization mechanism due to their different reproductive strategies and environmental pressures.